MODEL ONTOLOGI VARIETAS KELAPA SAWIT SEBAGAI DASAR SISTEM BERBASIS PENGETAHUAN RISET PERKEBUNAN - Arif Rakhman Hakim (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Knowledge is an important asset that is easily lost. This loss process has a significant impact on plantation research organizations whose research takes a long time. This research aimed to develop an ontology model for recording knowledge about oil palm varieties. In order to save knowledge, in this research nine oil palm varieties were modeled into ontology using the Web Ontology Language (OWL). Any information in oil palm varieties can be sorted and grouped into classes, object properties, data properties, or data expressions. The relationship between data in oil palm varieties can be well represented using ontology. Based on the results from HermiT reasoners, the ontologies with 43 classes are consistent. Information in the ontology of oil palm varieties can be easily rediscovered using the description logic query (DL-Query). The model produced from this research can be used as an initial model in designing knowledge management systems and ontology-based oil palm expert systems.Keywords: ontology, OWL, oil palm seed, knowledge management